2015
DOI: 10.1155/2015/587247
|View full text |Cite
|
Sign up to set email alerts
|

The Rapid Inactivation of Porcine Skin by Applying High Hydrostatic Pressure without Damaging the Extracellular Matrix

Abstract: We previously reported that high hydrostatic pressure (HHP) of 200 MPa for 10 minutes could induce cell killing. In this study, we explored whether HHP at 200 MPa or HHP at lower pressure, in combination with hyposmotic distilled water (DW), could inactivate the skin, as well as cultured cells. We investigated the inactivation of porcine skin samples 4 mm in diameter. They were immersed in either a normal saline solution (NSS) or DW, and then were pressurized at 100 and 200 MPa for 5, 10, 30, or 60 min. Next, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…We previously reported that HHP at 200 MPa for 10 min can inactivate mammalian cells, skin and melanocytic nevus tissue; however, those were not inactivated at HHP lower than 150 MPa [Mahara et al, 2014;Liem et al, 2015;Morimoto et al, 2015]. Therefore, we choose pressures of 100 and 200 MPa in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that HHP at 200 MPa for 10 min can inactivate mammalian cells, skin and melanocytic nevus tissue; however, those were not inactivated at HHP lower than 150 MPa [Mahara et al, 2014;Liem et al, 2015;Morimoto et al, 2015]. Therefore, we choose pressures of 100 and 200 MPa in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that HHP at 200 MPa for 10 min can inactivate mammalian cells and that it is capable of inactivating skin and melanocytic nevus tissue in light brown to black patches or plaques that contain nevus cells [Mahara et al, 2014;Jinno et al, 2015;Liem et al, 2015;Morimoto et al, 2015]. Giant congenital melanocytic nevi (GCMN), which are defined as nevi of more than 20 cm in diameter [Watt et al, 2004;Tannous et al, 2005;Zaal et al, 2005;Turkmen et al, 2010;Arad and Zuker, 2014], are reported to occur in approximately 1 in 20,000 newborns and have the risk of transforming into malignant melanomas in approximately 1-3% of individuals with GCMN [Tannous et al, 2005;Zaal et al, 2005;Arad and Zuker, 2014].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We are developing a novel skin regeneration therapy combining inactivation of the nevus via HHP (200 MPa) for the reconstruction of the dermis with CEA for the reconstruction of the epidermis . The advantage of this therapy is its use of autologous dermis, in which all cells including nevus cells have been inactivated using HHP . Despite concerns that the remaining debris from the inactivated cells may induce an inflammatory reaction, we have already shown that autologous porcine skin inactivated using HHP up to 1000 MPa was successfully engrafted for up to 4 weeks after grafting .…”
Section: Discussionmentioning
confidence: 99%
“…It is usually difficult to reconstruct skin defects after the removal of a GCMN, due to the shortage of available autologous skin grafts; therefore, it is also difficult to prevent the subsequent development of melanoma . To overcome this problem, we are developing a novel reconstruction treatment using the removed nevus tissue inactivated by high hydrostatic pressure (HHP) at 200 MPa for dermal reconstruction . We used a cultured epidermal autograft (CEA) via Green's method, which has been established since the 1970s, for the epidermal reconstruction in this treatment strategy.…”
Section: Introductionmentioning
confidence: 99%